The Break-Up Book Club - Wax, Wendy (New York : Berkley, 2021)
"The story of a book club of broken hearts, where four women come together and discover the power of female friendship and find the courage to pursue their dreams, from the USA Today bestselling author of My Ex-Best Friend's Wedding. Jazmine was supposed to be a professional tennis player, but her plans to go pro were quashed in a car crash. Now she's a top sports agent balancing a demanding career and single motherhood. Judith is an empty nester stuck in an unhappy marriage. After her husband's sudden death, she has to build a new life--one she never allowed herself to imagine--on top of the ashes of the old. When Sara finds out that her husband has left her for a secret second family in another city, she believes she's hit rock bottom...until her husband steals all of his mother's money, and Sara gets a new roommate--her mother-in-law. Erin was a week away from marrying her high school sweetheart when her fiancé called off the wedding. Heartbroken, Erin is forced to navigate adulthood as a single woman for the first time. Once a month, these women meet in a historic carriage house in Atlanta seeking solace, friendship, and people who share their love of books (okay, and wine). Together, with a lot of inspiration from their favorite books, they help one another move forward, to discover who they want to be now and what will make them happy"--.